TEACHING PRIPNCIPLES OF PHYSICS HISTORY IN SECONDARY SCHOOLS - Saydayev, Obid (Физико-технологического образование, 2023)
In this article we discuss the problem of physics history in educational system. On the issue of physical education in the 21st century, it was noted that even graduate students do not have a correct understanding of the significance of the most important works of domestic scientists. Students have poor knowledge of the factual material about the life and work of a particular scientist; confuse the names of scientists, attribute to them other people’s inventions; cannot name the names of domestic scientists. All this once